Răspuns :
a) 6x-8+30x-35-3x=9x+90+11x+132+8
6x+30x-3x-9x-11x=90+132+8+8+35
13x=273
x=273:13
x=21
b) 18x-15-8x-6+13=8x-18+2x-15x+10
18x-8x-8x-2x+15x= -18+10+15-13
15x=30
x=30:15
x=2
6x+30x-3x-9x-11x=90+132+8+8+35
13x=273
x=273:13
x=21
b) 18x-15-8x-6+13=8x-18+2x-15x+10
18x-8x-8x-2x+15x= -18+10+15-13
15x=30
x=30:15
x=2
a) 2(3x-4)+5(6x-7)-3x=9(x+10)+11(x+12)+8
6x-8+30x-35-3x=9x+90+11x+132+8
33x-43=20x+230
13x=273
x=21
b) 3(6x-5)-2(4x+3)+13=-2(-4x+9)+2x-5(3x-2)
18x-15-8x-6+13=8x-18+2x-15x+10
18x-8x-8x-2x+15x=-18+10+15+6+-13
15x=0
x=0
6x-8+30x-35-3x=9x+90+11x+132+8
33x-43=20x+230
13x=273
x=21
b) 3(6x-5)-2(4x+3)+13=-2(-4x+9)+2x-5(3x-2)
18x-15-8x-6+13=8x-18+2x-15x+10
18x-8x-8x-2x+15x=-18+10+15+6+-13
15x=0
x=0